Lessons from implementing integrated water resource management: a case study of the North Bay-Mattawa Conservation Authority, Ontario. Issue 3 (4th May 2017) - Scott, Paula; Tayler, Brian; Walters, Dan
Abstract: This case study explores the North Bay-Mattawa Conservation Authority's experience in implementing IWRM. Successes include protecting life and property by mitigating flood and erosion hazards; building capacity through multi-stakeholder collaborations; and fostering community stewardship. Ongoing challenges include limited resources and narrow mandate for addressing broader watershed and natural resources issues; and a need to enhance relationships with First Nations. The NBMCA has learned numerous lessons on how to apply IWRM, including collaborating early and often and fostering community stewardship.